A national survey examining recognition, demand for antivenom, and overall level of preparedness for redback spider bites in Japan. Issue 4 (18th April 2016) - Hifumi, Toru; Okazaki, Tomoya; Manabe, Arisa; Hamaya, Hideyuki; Egawa, Satoshi; Fujimi, Satoshi; Yamamoto, Akihiko; Koido, Yuichi; Abe, Yuko; Kawakita, Kenya; Umezawa, Kazuo; Kuroda, Yasuhiro
Abstract : Aim: Redback spiders are rapidly becoming a nationwide problem in Japan. The domestic production of antivenom for redback spider bites has been started because of extremely low supply. The purpose of this study was to investigate the ability of emergency physicians to recognize redback spider bites and to examine the demand for antivenom and identify the ideal choice for storage. Methods: Questionnaires examining the ability to recognize redback spider bites, the demand for antivenom, and overall level of preparedness were sent to 271 emergency medical service centers in Japan in March 2015. Results: Completed questionnaires were returned by 156 medical institutions (58%). Only 25% of the institutes correctly answered regarding the recognition of redback spider bites. A demand for the new, domestically produced antivenom was reported by 55% of the institutes. Antivenom demand was high and increased with the ability to recognize redback spider bites (0 correct answers, n = 24 [42.9%]; 1–2 answers, n = 32 [55.2%]; three answers, n = 28 [71.8%]; P = 0.02). The storage of antivenom within their prefectures or regions was the best option for initial supply planning. Approximately 90% of the emergency centers showed an ability to use the antivenom safely. Conclusion: The recognition of redback spider bites was low; however, the demand for antivenom was high. The storage of antivenom within their own prefectures or regions was considered to be the best option for initial supply planning. Emergency medical service centers are also good candidates for storage and safe use of antivenom.